France, film and the Holocaust : from "le génocide" to "la shoah" - Banaji, Ferzina (Studies in European culture and history, 2012)
Representing the "un-representable" -- Resistance, and repression (1940 -1960) -- Revisiting collaboration: Vichy and the Holocaust (1960-1980) -- From Lanzmann's Shoah to la shoah (1985-2000) -- A "century of genocide" and beyond (2000 ) -- Conclusion